Home delivery and associated factors among women who gave birth after antenatal care follow-up in the last 6 months in Jabitehnan District, Northwest Ethiopia: mixed community-based study - Aynalem, Bewket Yeserah; Zerihun, Tamene; Alemu, Addisu Alehegn; Meselu, Belsity Temesgen; Zeleke, Liknaw Bewket; Kassa, Getachew Mullu (Frontiers in Global Women's Health, 2024)
IntroductionMaternal mortality is a global issue, with developing countries accounting for over 99% of maternal deaths, with 30% of Ethiopian mothers dying from pregnancy-related causes. This study aimed to assess the magnitude, associated factors, and reasons for home delivery among women who gave birth after antenatal care follow-up in the last 6 months in Jabitehnan District, Northwest Ethiopia.MethodsA mixed community-based study was conducted on women who gave birth after antenatal care follow-up in the last 6 months. Data was collected through face-to-face interviews and structured questionnaires. Bivariate and multivariable logistic regressions were performed to identify factors associated with home delivery. Qualitative data were collected through focus group discussions and in-depth interviews and analyzed using a thematic content analysis method.ResultIn this study, the magnitude of home delivery after ANC follow-up among mothers who gave birth in the last 6 months was 37%, with a 95% CI of 32.5 and 41.5. Pregnancy plan [AOR: 4.56 (2.65, 7.86)], experience of abortion AOR: 3.01 [1.631, (5.55)], ANC follow-up at public hospitals [AOR: 1.89 (1.119, 3.18)], and pregnant mothers visited at home by healthcare providers during their ANC follow-up absent [AOR: 1.61 (1.02, 2.53)] were predictors of home delivery. Poor counseling during ANC, and lack of pregnancy plans, traditions, and beliefs were reasons for home delivery.ConclusionThe study reveals a high magnitude of home delivery as compared to a study done in Bahir Dar (21.2%). Factors include pregnancy plans, health institution type, abortion experience, and absence from antenatal care. Poor counseling during ANC, and lack of pregnancy plans, traditions, and beliefs were reasons for home delivery. Health professionals should receive training in communication and counseling techniques, and they should encourage mothers to plan their pregnancies and visit facility delivery services during ANC follow-up.